Normative Legal Research Methodology from the Experts' Perspective: A Comparative Analysis of Concepts and Approaches - Putri Wulandari (PT. AVID MEDIA INDONESIA, 2026)
Normative legal research is the dominant approach in the Indonesian legal scholarly tradition, but the use of terms and approaches is often not accompanied by precise methodological explanations. This condition creates conceptual ambiguity that has implications for the weak construction of scientific arguments. This study aims to comparatively analyze the conceptualization of normative legal research according to experts and reconstruct its methodological boundaries to be more systematic and operational. The method used is normative legal research with a conceptual and comparative approach, through a literature study of primary, secondary, and tertiary legal materials. The analysis is conducted qualitatively using descriptive-analytical and argumentative techniques to test the logical consistency, systemic coherence, and prescriptive power of each approach. The results of the study indicate that normative legal research cannot be reduced to a textual review of laws and regulations but must combine legislative, conceptual, historical, and comparative approaches within the framework of the hierarchy of norms and legal principles. The method of interpretation and construction of legal arguments are central instruments for overcoming normative ambiguity and maintaining prescriptive validity. Integrative methodological reconstruction produces a more coherent, principle-based normative research model, and is able to provide rational and scientifically accountable legal solutions.